Peningkatan Ekonomi Masyarakat: Dampak Pemanfaatan Ampas Susu Kedelai Menjadi Nugget - Laila Puspita; Komarudin Komarudin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Soy milk is one of the processed products of soybean which has multi function for body health so it is safe to consume for daily drink. In Desa Banjarsari of Talang Padang District, there is the soy milk industry, when producing soy milk leaving soybean pulp. The purpose of this activity is to increase the community's economy through the utilization of soy milk residue into nuggets. The methods undertaken are by way of approach, practice, counseling, technical guidance, and mentoring. From this activity, it is known that the participants enthusiastically from PKK mothers to acquire the skills and ability to use soy milk pulp as an processed product in the form of nutritional-rich nuggets. The stimulus to increase the community's economy was well-responded by the participants, thereby providing hope for the improvement of quality of animal food consumption and opening opportunities to PKK mothers to carry out continuing continuity and sustainability activities so that PKK mothers can be built.